PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFORMING LOAN (NPL) TERHADAP PROFITABILITAS ROA PADA PT BANK CENTRAL ASIA TBK - Nina Sabrina; Rita Satria; Ratna Sari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to determine the effect of the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) Against Return On Assets (ROA) either partially or simultaneously. The research design used in the preparation of this research is causal associative quantitative which aims to determine the effect of the independent variables on the dependent variable in depth describing or revealing problems, situations, events or revealing facts and trying to find solutions or problem solving. The effect Capital Adequacy Ratio (CAR) on Return On Assets (ROA) at PT Bank Central Asia Tbk has a significant effect between the Capital Adequacy Ratio (CAR) variable on the Return On Assets (ROA) variable seen from the significance value of 0,047 which is smaller than the limit value significance of 0,05.